2000
DOI: 10.1081/ada-100100601
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Treatment Outcomes in Men and Women Admitted to a Therapeutic Community

Abstract: This study compared factors that predict treatment outcomes in men and women randomly assigned to two therapeutic communities differing primarily in length of inpatient and outpatient treatment. Based on the prior research literature comparing treatment outcomes of men and women, we formulated the following research question: Do factors that predict drug use at follow-up, postdischarge arrest, and employment at follow-up differ for men and women? Self-reports and objective measures of criminal activity and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
2
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 14 publications
3
117
2
3
Order By: Relevance
“…Related work (Messina et al, 2000) found that history of physical abuse predicted positive urine drug screens at follow-up for women, but not for men. Conversely, Fiorentine and colleagues (1999) found few differences in men's and women's outcomes when examining history of abuse; when they did find a difference, abuse predicted only men's outcomes .…”
Section: History Of Victimizationmentioning
confidence: 98%
“…Related work (Messina et al, 2000) found that history of physical abuse predicted positive urine drug screens at follow-up for women, but not for men. Conversely, Fiorentine and colleagues (1999) found few differences in men's and women's outcomes when examining history of abuse; when they did find a difference, abuse predicted only men's outcomes .…”
Section: History Of Victimizationmentioning
confidence: 98%
“…Although evidence indicates that treatment does indeed lead to continued abstinence for a number of individuals (Gossop, Marsden, Stewart, & Treacy, 2002;Hubbard, Craddock, Flynn, Anderson, & Etheridge, 1997;Messina, Wish, & Nemes, 2000), a large percentage of individuals entering treatment for substance abuse either dropout of treatment early or relapse soon after treatment termination (Carmichael, Linn, Pratt, Ted, 1977;Crits-Christoph & Siqueland, 1996;Hubbard et al, 1997;Ravndal & Vaglum, 2002;Simpson, Joe, & Brown, 1997). This is especially true in long term residential treatment which has the lowest rate of completion compared to other treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from specific therapies, some studies stated that post-rehabilitation support was provided, usually in the forms of community based intervention or a monitored halfway house (Carroll & McGinley, 2000). One study included aftercare as part of the measured longitudinal data (Messina, Wish, & Nemes, 2000), but did not report the specific effect of aftercare. Overall, insufficient information was reported to compare program types, or services provided.…”
Section: Investigated Treatment As Usual (Tau) As Compared Tomentioning
confidence: 99%
“…A pair of studies engaged previously graduated residents a mean of 6 years after graduation (Fernández -Montalvo et al, 2008;Fernández-Montalvo et al, 2007). A further two studies included post program time points as part of longitudinal research, with a mean follow-up length of 17 months (Dekel et al, 2004;Messina et al, 2000). No other followups were reported.…”
Section: Retention and Dropout As Well As Mean Length Of Stay In Treamentioning
confidence: 99%
See 1 more Smart Citation